Three-Year Multicenter Analysis of HIV Infection Diagnostic Data - Karatas, Aysel; Kuskucu, Mert Ahmet; Ordekci, Seyhan; Can, Rabia; Karalti, Iskender; Ozdemir, Baran; Celik, Gulden (Ankara Microbiology Soc, 2025)
The three step human immunodeficiency virus (HIV) testing algorithm used in T & uuml;rkiye was updated and implemented in 2019 in accordance with the current HIV testing algorithm of the Centers for Disease Control and Prevention. In this study, it was aimed to obtain HIV test data with a multicenter and multidisciplinary approach in order to reveal the current situation in the diagnosis of HIV/acquired immunodeficiency syndrome in our country and to identify new algorithm applications and problems encountered in HIV diagnosis. For this purpose, 12 HIV testing centers were asked about the HIV testing algorithms they use, the problems they encountered in practice and their suggestions for solution with a 57-question survey. The performance of the current algorithm and the current HIV status of the centers were evaluated with the total number of three-year fourth generation HIV enzyme linked immunsorbent assay ([LISA) tests , the number of repeated reactive tests, the distribution of confirmatory test results and the number of HIV nucleic acid amplification tests (NAT) between 2018 and 2020. Between 2018 and 2020, the total number of anti-HIV [LISA tests were 788261, 871299 and 835498, the repeating reactivity rates were 0.48, 0.51 and 0.70, respectively, while the confirmed HIV test rates were 0.24, 0.25 and 0.21 respectively. During this period the rates of Western Blot (WB) confirmatory test utilization were 25.77%, 12.29% and 9.86%, respectively and are gradually decreasing. The utilization rates of HIV-1/2 antibody differential rapid confirmatory tests recommended in the current algorithm were found to be 25.72%, 38.76% and 45.78%, respectively and it is seen to replace WB. The rates of HIV-1 RNA studied by year were 48.77%, 97.98% and 46.31% respectively. In our study, it has been observed that the use of the rapid HIV-1/2 antibody differential test, which is included in the new algorithm, is gradually increasing and is used more effectively in HIV diagnosis, while the use of HIV-1 NAT has decreased. This situation, which is associated with the shift of NAT opportunities to coronavirus diseases-2019 (COVID-19) polymerase chain reaction studies in the shadow of the COVID-19 pandemic, requires more detailed monitoring in terms of possible changes in the HIV epidemic in our country.
Keywords: HIV; HIV Algoritm; HIV/AIDS Serodiagnosis; HIV Seroprevalence; HIV-1 NAT